Amplification of the Insulin-Like Growth Factor 1 Receptor Gene Is a Rare Event in Adrenocortical Adenocarcinomas: Searching for Potential Mechanisms of Overexpression. (10th July 2014) - Ribeiro, Tamaya Castro; Jorge, Alexander Augusto; Almeida, Madson Q.; Mariani, Beatriz Marinho de Paula; Nishi, Mirian Yumi; Mendonca, Berenice Bilharinho; Fragoso, Maria Candida Barisson Villares; Latronico, Ana Claudia
Abstract : Context . IGF1R overexpression appears to be a prognostic biomarker of metastatic pediatric adrenocortical tumors. However, the molecular mechanisms that are implicated in its upregulation remain unknown. Aim . To investigate the potential mechanisms involved in IGF1R overexpression. Patients and Methods . We studied 64 adrenocortical tumors. IGF1R copy number variation was determined in all patients using MLPA and confirmed using real time PCR. In a subgroup of 32 patients, automatic sequencing was used to identify IGF1R allelic variants and the expression of microRNAs involved in IGF1R regulation by real time PCR. Results . IGF1R amplification was detected in an adrenocortical carcinoma that was diagnosed in a 46-year-old woman with Cushing's syndrome and virilization. IGF1R overexpression was demonstrated in this case. In addition, gene amplification of other loci was identified in this adrenocortical malignant tumor, but no IGF1R copy number variation was evidenced in the remaining cases. Automatic sequencing revealed three known polymorphisms but they did not correlate with its expression. Expression of miR-100, miR-145, miR-375, and miR-126 did not correlate with IGF1R expression. Conclusion . We demonstrated amplification and overexpression of IGF1R gene in only one adrenocortical carcinoma, suggesting that these combined events are uncommon. In addition, IGF1R polymorphisms and abnormal microRNA expression did not correlate with IGF1R upregulation in adrenocortical tumors.